Strategi Customer-Centric dalam Marketing: Dampaknya pada Loyalitas dan Retensi Pelanggan - Hery Derajad Wijaya (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In the era of economic globalization, companies face complex challenges in meeting the ever-evolving needs of customers. The customer-centric strategy, which focuses on a deep understanding of customer preferences and experiences, has become increasingly relevant amidst intense competition and advancements in information technology. This study aims to explore the impact of customer-centric strategies on customer loyalty and retention in the retail and e-commerce sectors. Using a quantitative approach, data was collected through a survey of 200 customers who had interacted with the company for over a year. Multiple regression analysis showed that the variables of product quality, service personalization, effective communication, and overall customer experience had a significant impact on customer loyalty. The findings highlight the importance of service personalization and relevant communication in building long-term customer relationships. These results provide strategic insights for companies to develop customer-centric marketing policies to enhance customer satisfaction and loyalty. The study also emphasizes the need for technology integration in implementing these strategies to address dynamic market challenges and ensure business sustainability.